2014
DOI: 10.2135/cropsci2014.01.0028
|View full text |Cite
|
Sign up to set email alerts
|

Winter Wheat Eastern European Regional Yield Trial: Identification of Superior Genotypes and Characterization of Environments

Abstract: The International Winter Wheat Improvement Program (IWWIP)—a collaboration between the government of Turkey, the International Maize and Wheat Improvement Center (CIMMYT), and the International Center for Agricultural Research in the Dry Areas (ICARDA)—develops and globally distributes improved winter wheat (Triticum aestivum L.) germplasm. The Winter Wheat Eastern European Regional Yield Trial was conducted by IWWIP during 1998–2005 using elite lines and varieties from IWWIP, Eastern Europe (EE), the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…There is a more complex influence of weather conditions on the quality parameters of winter wheat compared to spring wheat (Johansson and Svensson, 1998). Winter bread wheat growing environments in Central Asia are diverse (Sharma et al, 2014a) and there is a significant effect of environment and genotype × environment (GE) interaction on grain yield under both irrigated (Sharma et al, 2010) and rainfed (Sharma et al, 2012) conditions. Similar findings on the effect of GE interaction on wheat grain yield have been reported for the surrounding regions (Osmanzai and Sharma, 2008;Sakin et al, 2011;Sharma et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…There is a more complex influence of weather conditions on the quality parameters of winter wheat compared to spring wheat (Johansson and Svensson, 1998). Winter bread wheat growing environments in Central Asia are diverse (Sharma et al, 2014a) and there is a significant effect of environment and genotype × environment (GE) interaction on grain yield under both irrigated (Sharma et al, 2010) and rainfed (Sharma et al, 2012) conditions. Similar findings on the effect of GE interaction on wheat grain yield have been reported for the surrounding regions (Osmanzai and Sharma, 2008;Sakin et al, 2011;Sharma et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Henn. ), and several agronomic traits (Sharma et al, 2014) (Supplemental Table S1). Sharma et al (2014) identified 56 superior genotypes from 8 yr of the WWEERYT, but a seed sample was available for only 35 of the 56 superior genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…I nternational exchange of improved germplasm is important in addressing existing and emerging constraints to global wheat ( Triticum aestivum L.) production. Elite breeding lines tested in international performance nurseries represent the most advanced materials from a collection of breeding programs and best showcase a pool of genotypes for cultivar release or use as parents in future crosses (Peterson and Pfeiffer, 1989; Sharma et al, 2010, 2012, 2014). The International Winter Wheat Improvement Program (IWWIP) is a cooperative breeding program between the Ministry of Agriculture and Rural Affairs of Turkey, the International Maize and Wheat Improvement Center (CIMMYT), and the International Center of Agricultural Research in the Dry Areas (ICARDA) (Morgounov et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In collaboration with Oregon State University, IWWIP operated Winter Wheat Eastern European Regional Yield Trial (WWEERYT) in 1998-2005 using elite lines and cultivars from IWWIP, Eastern Europe (EE), the USA and CWA. A study by Sharma et al [18] analyzed data to identify superior genotypes and key locations that could be useful for future international collaboration on winter wheat. Grain yield and agronomic traits of 422 elite breeding lines and new cultivars from 17 countries were evaluated across 39 locations.…”
Section: Research Highlightsmentioning
confidence: 99%